IN MEMORIAM (PANGEEA, 2025)
An obituary commemorating Marcian David Bleahu (1924-2019), Romanian geologist, speleologist, geographer, mountaineer, explorer, writer, and politician. The piece outlines his career at the Geological Institute of Romania, his influence on global tectonics studies and cave science, his role in founding and managing the National Geology Museum in Bucharest, and his leadership in environmental policy and ecology in Romania. It highlights his contributions to science communication and public engagement, and notes his international recognition in 1992 as vice-president of the United Nations Conference on Environment and Development.
Keywords: In Memoriam; Marcian Bleahu; Geology; Speleology; Geography; Environment; Romania; Biography